Nas margens do Rio Piracicaba: o pescador e outras temporalidades da Rua do Porto - Camargo, Fernando Monteiro [UNIFESP] (2016)
The focus of this research is the relationship that multiple actors create in and with the urban space. The site chosen for the survey is Rua do Porto, which is located on the banks of the Piracicaba river, in the city that bears the same name, in the state of São Paulo, Brazil. During the research process, I incorporated the use of photographic equipment, which provided a shift in my look at the field. I prepared a map of my research experience, combining drawing and photography to my written records and life experiences. In my imagery experience, I found the fisherman, a character that unites both present and past and survives on the banks of the Piracicaba river.